The dalit Christians : a history - Webster, John C. B., 1935- (Delhi : ISPCK, 1994)
Study of Christians belonging to economically backward and socially underprivileged classes in India.
Includes bibliographical references (p. [249]-267) and index.
Keywords: Christianity -- India; Christians -- India -- Social conditions; India -- Church history